Management induced changes of antibiotic resistant strains of heterotrophic bacteria in shrimp farming ponds - JANA, T K; BANERJEE, R D; LAHIRI, SUSMITA; JANA, B B (The Indian Journal of Animal Sciences, 2014)
Antibiotic resistant strains of heterotrophic bacteria and total aerobic heterotrophic bacteria were enumerated along with important water quality parameters in water and sediment samples collected from 3 shrimp farming ponds used for the monoculture of Penaeus monodon as well as from a control pond located outside the shrimp farm. The resistant strains of heterotrophic bacteria were screened against 3 antibiotics (ampicillin, chloramphenicol and oxytetracycline) at 25 and 50 μg/l. The counts of antibiotic resistant bacteria tended to rise in shrimp ponds with progressive rise in the days of culture, but were specially high during the period when both antibiotics and feed were applied in the system. It appears that antibiotics exerted a selective pressure in favour of antibiotic resistant bacterial strains and widespread use of antibiotics should be forbidden in shrimp ponds.